Evaluation of adiponectin and resistin levels in gingival crevicular fluid in patients with chronic periodontitis before and after treatment: A clinico-biochemical study - P Fairlin; S A Jacob Raja; Johnson Raja James; Tamil Selvan Kumar; Ravi Shankar; S Divya (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to find out the association of adiponectin and resistin levels in gingival crevicular fluid (GCF) with the clinical parameters before and after scaling and root planing in periodontitis patients. Methods: A total of 50 patients were recruited from the Outpatient Department of Periodontics, JKK Nattraja Dental College and Hospital, Komarapalayam, Tamil Nadu, India. The protocol was reviewed and approved by the institutional ethical board. Informed consent was obtained from the patients and the study-related procedures were explained. Patients were divided into two groups. Group I (25 patients) consisted of healthy patients. Group II (25 patients) consisted of periodontitis patients. The periodontitis patients after treatment were considered as Group III. GCF samples were collected before treatment and 21 days after treatment. The levels of adiponectin and resistin were evaluated using Immunotag™ Human RETN enzyme-linked immunosorbent assay (ELISA) kit (ITEH0269) and Immunotag™ Human ADP (adiponectin) ELISA kit (ITEH2593). The levels were correlated with the clinical parameters. Results: There were an increase in the mean adiponectin level and a decrease in the mean resistin level at the end of periodontal therapy. Conclusions: Adiponectin which is an anti-inflammatory component was found to increase after periodontal therapy, and resistin which is an inflammatory component has been decreased after periodontal therapy.